Pengembangan Pop-Up Book berbasis Augmented Reality Materi Bangun Ruang Meningkatkan Self Efficacy Siswa Kelas V SDN Sumberdiren 01 Kabupaten Blitar - Wijono, Alifa Putri Sasmita Hadi; Alfi, Cindya; Fatih, Mohamad (Universitas Nusantara PGRI Kediri, 2024)
The goal of this project is to improve the self-efficacy of 5th grade students through the development of augmented reality-based pop-up book learning materials and building spaces. Research and development (R&D) methodology is used in this project. The data was collected using surveys and interviews with instruments assessed by language, media, and material experts. The assessment from language experts received a score of 82.5%, meaning